Penyelenggaraan Ibadah Haji Indonesia dalam Perspektif Maq?????id Asy-Syar?????ah - Muhammad Hosnan Jaini Sanusi (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2021)
The hajj implementation in Indonesia is seen discriminative by some Moslems in Indonesia in view of the classification of hajj into regular hajj, special hajj and Mujamalah hajj. This research aims to (1) observe the condition of the hajj implementation in Indonesia in the perspective of Maq?????id asy-Syar?????ah; and (2) figure out and analyze the purpose (maq?????id) of the classification of hajj implementation into regular hajj, special hajj and Mujamalah hajj. This qualitative research is included as library research (maktabiyah) with the research objects in the form of important documents, legislations related to the hajj implementation equipped with adequate field research (maid??niyah) as support. As a framework, Maq?????id ash-Syar??'ah theory. Also, the theory of legal politics was used as a supporting theory. The results of the study concluded that: First, the hajj implementation in Indonesia in the perspective of Maq?????id ash-Syar??'ah becomes a part of the Maq?????id ash-Syar??'ah with the arguments: a) the ar??riyy??t regulations for the hajj implementation in Indonesia is needed by the Indonesian Muslims as a base in doing the pilgrimage; b) the hajj implementation in Indonesia maintains five main objectives of sharia to preserve: religion, soul, mind, lineage and property. Second, the classification of the hajj into regular hajj, special hajj and mujamalah hajj, based on Maq?????id ash-Syar??'ah theory and legal political theory is a manifestation of justice and government policy in organizing the hajj. Thus, the classification of the hajj implementation in Indonesia aims to: a) benefit (li al-ma???la???ah), b) justice (li al-???ad??lah), and c) convenience (li at-tais??r).